Network Meta-Analysis of Different Acupuncture Therapies in Treatment of Low Back Myofascitis - GE Haiya; YAN Laijun; YANG Zongrui; SHI Jinyu; ZHAN Hongsheng (康复学报)
ObjectiveTo evaluate the efficacy of different acupuncture therapies for low back myofascitis through network meta-analysis.MethodsRandomized controlled trials (RCTs) of acupuncture therapy for low back myofascitis were retrieved from CNKI, Wanfang, VIP, PubMed, Embase, Cochrane Library from inception to April 2022. Outcome measures included overall efficiency and visual analogue scale (VAS). Literature screening and data extraction were carried out independently by two researchers, and the literature quality was evaluated according to the Cochrane reviewer's Handbook. Stata 15.0 was used to draw network plots of each acupuncture therapy and the publication bias funnel plots of the included literature. GEMTC 0.14.3 was used to conduct network meta-analysis for each therapy; and continuous variables were described by mean difference (MD), and dichotomous variables were described by the odds ratio (OR). If the nodes of included studies showed good consistency after analysis (P>0.05), the consistency model was used for data analysis, and the probability ranking diagram of each acupuncture therapy was drawn. If the nodes of included studies had poor consistency after analysis (P<0.05), the non-consistency model was used for data analysis.ResultsA total of 41 RCTs were included with 6 258 patients, involving eight kinds of acupuncture therapies, including electroacupuncture, akupotomye, warming needle moxibustion, acupuncture, subcutaneous needling, acupoint catgut embedding, moxa-wool moxibustion and blood-letting puncturing. (1) Total effective rate: all included acupuncture therapies were more effective than western medication (P<0.05); akupotomye, subcutaneous needling, and acupoint catgut embedding were all more effective than acupuncture (P<0.05); akupotomye, warming needle moxibustion, subcutaneous needling, acupoint catgut embedding were all more effective than electroacupuncture (P<0.05). (2) VAS score:the VAS scores of akupotomye, warming needle moxibustion, subcutaneous needling acupoint catgut embedding, moxa-wool moxibustion were lower than that of electroacupuncture (P<0.05); and the scores of akupotomye, acupoint catgut embedding, moxa-wool moxibustion were lower than that of acupuncture (P<0.05). The VAS scores of akupotomye, warming needle moxibustion, subcutaneous needling, acupoint catgut embedding, moxa-wool moxibustion were all lower than that of western medication (P<0.05). The probability ranking diagram of intervention measures of each acupuncture therapy showed that the acupoint catgut embedding was the most likely to be the best therapy measure (P<0.05).ConclusionThe therapeutic effect of acupuncture therapies on low back myofascitis is better than that of western medication, and acupoint catgut embedding has the best curative effect.